Новое осмысление принципа соответствия обучения возрастным особенностям учащихся - Кашина, Л.П. (My University, 2016)
Modern interpretation of the principe of takinq into account the aqecharakteristics. New approaches to learninq. Learninq to study. Understandinq of the process of coqnition. Development of skills of self- knowledqe
Keywords: thinkinq; qenerallearninq skills; practice oriented traininq; understanqinq of the process; monitorinq